2022
DOI: 10.3390/cancers14041043
|View full text |Cite
|
Sign up to set email alerts
|

The Antianginal Drug Perhexiline Displays Cytotoxicity against Colorectal Cancer Cells In Vitro: A Potential for Drug Repurposing

Abstract: Colorectal cancer (CRC) is the second leading cause of cancer-related death worldwide. Perhexiline, a prophylactic anti-anginal drug, has been reported to have anti-tumour effects both in vitro and in vivo. Perhexiline as used clinically is a 50:50 racemic mixture ((R)-P) of (−) and (+) enantiomers. It is not known if the enantiomers differ in terms of their effects on cancer. In this study, we examined the cytotoxic capacity of perhexiline and its enantiomers ((−)-P and (+)-P) on CRC cell lines, grown as mono… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 38 publications
1
10
0
Order By: Relevance
“…It is not clear if these other pathways reported to be altered by PHX in cancer cells are specific primary targets or are activated as a downstream effect of its binding to CPT1 or are a consequence of cell damage or death resulting from the drug. Because of its inhibitory effects on cancer cells in a number of experimental models, there is interest in whether PHX has the potential to be repurposed as an adjunctive therapeutic in the management of cancer (46)(47)(48).…”
Section: Discussionmentioning
confidence: 99%
“…It is not clear if these other pathways reported to be altered by PHX in cancer cells are specific primary targets or are activated as a downstream effect of its binding to CPT1 or are a consequence of cell damage or death resulting from the drug. Because of its inhibitory effects on cancer cells in a number of experimental models, there is interest in whether PHX has the potential to be repurposed as an adjunctive therapeutic in the management of cancer (46)(47)(48).…”
Section: Discussionmentioning
confidence: 99%
“…It has been revealed that the antifungal agent oxiconazole induces anti-tumor effects in CRC cells by inhibiting autophagy through downregulation of peroxiredoxin-2 ( PRDX2 ), leading to growth suppression, and suggests its potential therapeutic use in combination with oxaliplatin for CRC treatment ( Shi J. et al, 2022 ). Moreover, Dhakal et al (2022) investigated the cytotoxic effects of the anti-anginal drug perhexiline and its enantiomers on CRC cells and demonstrated their ability to induce apoptosis and reduce cell viability in both monolayers and spheroids, as well as patient-derived organoids ( Dhakal et al, 2022 ). Liñares-Blanco et al (2020) proposed abemaciclib, an inhibitor of the CDK4/6 protein, as a promising option for the treatment of colon cancer ( Liñares-Blanco et al, 2020 ).…”
Section: Repurposed Drugs For Gastrointestinal Cancers Treatmentmentioning
confidence: 99%
“…For this reason, treatment options based on combination regimens have been tested. Although FAO inhibition alone can trigger compensatory activation of other metabolic pathways, FAO inhibitors can also synergize with conventional antitumor agents such as paclitaxel [91] . For example, FAO and OXPHOS are increased in cytarabine-resistant AML cells; FAO inhibition with etomoxir induced a metabolic shift from high to low OXPHOS, sensitizing the cells to cytarabine [66] .…”
Section: Fao Of Aml Cells In the Bm Microenvironmentmentioning
confidence: 99%
“…Etomoxir is a pharmacological inhibitor of CPT1A, one of the isoforms of CPT1 [ 89 ] , frequently used to block free fatty acids from entering the mitochondria via CPT1. Although the clinical use of etomoxir has ceased because of adverse effects [ 90 ] , the CPT1 inhibitor perhexiline can sensitize breast cancer cells to paclitaxel [ 91 ] , and other CPT1 inhibitors [ 92 ] are currently being investigated for use in cancer therapy. The CPT1A inhibitor ST1326 has been shown to cause cell growth arrest, mitochondrial damage, and apoptosis in AML cells in a dose- and time-dependent manner [ 67 ] .…”
Section: Main Textmentioning
confidence: 99%